Myth, Memory, and the Architecture of Coexistence: The Case of El-Ghriba Synagogue, Tunisia - Mansour, Nesrine (2026)
Keywords: Judaïsme – Djerba

The Trajectories of Separation: Transatlantic Networks, Disciplinary Boundaries, and the Isolated Histories of Mizrahim - Gerber, Noah S.; Moreno, Aviad (AJS Review: The Journal of the Association for Jewish Studies, 2025)
Most sociological and ethnographical studies of Israeli Mizrahim are disconnected from those of Sephardic and MENA Jewish communities worldwide. Rooted in academic cultures that predate the country's establishment, Mizrahi history in Israel is often deemed either a success story or a shameful story of marginalization in these communities' global histories, and as a sui generis case of Jewish migration. We trace the early origins of this seemingly arbitrary disconnect to nineteenth-century European scholarship on "Sephardic" turned "Oriental" Jews and follow its subsequent entrenchment not only in Mandate Palestine and Israel but also in the United States. By focusing on key scholars working across transregional networks, we show how a Sephardic bias evolved into disciplinary divisions that have constrained the development of MENA Jewish studies. Finally, we call for renewed attention to the historical and contemporary patterns of separation, diffusion, and diasporic mobility that have long characterized MENA Jewish communities.
Keywords: Judaïsme – Djerba; Judaïsme – Mzab

Aliza Mamo's life of resilience and faith - Meir, Sivan Rahav (The Jerusalem Post, 2025)
Family of Aliza Mamo, soon turning 106, shares her inspiring journey from Djerba to Israel.
Keywords: Emigration – Djerba – Palestine; Judaïsme – Djerba

Tunisians demand accountability for dual citizen who served in Israeli army during Gaza war (Middle East Monitor, 2025)
Dozens of Tunisians have demanded accountability for a Tunisian-Israeli citizen who served in the Israeli occupation army during the war on the besieged Gaza Strip. Photos and videoclips of a Tunis…
Keywords: Guerre de Gaza (2023-....); Judaïsme – Djerba

Polémique en Tunisie : Un chanteur d’origine juive apparu en uniforme de l’armée israélienne (2025)
Le chanteur tunisien d’origine juive, identifié comme Sahi Maimoun, est au centre d’une vive controverse après la diffusion d’images le
Keywords: Guerre de Gaza (2023-....); Judaïsme – Djerba

‘Comme à Tunis’: Roundtable with Rafram Chaddad - Jonathan, Victoria (Francosphères, 2025)
‘Comme à Tunis’ was an evening curated by Victoria Jonathan around the work of Tunisian artist Rafram Chaddad, on 14 October 2024 at the Book Bar (Hôtel Grand Amour), in conjunction with Paris Art Week. Drawing on everyday life and investing public spaces, Rafram’s work evokes exile, migration, the fragility of borders, and the mutability of identities. This roundtable, co-chaired with Joseph Hirsch (mahJ), focuses on Rafram Chaddad’s book The Good Seven Years, a deeply original artistic work on the traces of Tunisia’s Jewish minority that almost disappeared in the twentieth century.
Keywords: Judaïsme – Djerba

Les (échelles de) proximité(s) d’un snack cacher du souk de Djerba - Morvan, Yoann (Géoproximités, 2025)
Keywords: Judaïsme – Djerba

Jewish Communities in French North Africa: Comparing Strategies and Outcomes - Petrucci, Filippo; Soi, Isabella (The Maghreb Review, 2025)
The article describes Jewish communities’ stances in relation to Zionist movements in France and in territories administered by France that were primarily populated by Muslims. It considers the actions of North Africa Jews in the Zionist movement, particularly during the Second World War, and how the war influenced Zionism. The Jewish communities in Algeria, Morocco, and Tunisia had different statuses influenced by and mirrored in the various colonial administrations, local authorities, and populations. Besides, those differences related to their degree of involvement with Zionism, which was anything but homogeneous and ranged from strong support to a lack of interest. Based on material collected from various archives (mainly Yad Vashem and the Central Zionist Archives), the article uses a selection of testimonies that describe the diversity of North African Jewish communities and their different levels of engagement with Zionist activities. In this way, the stories of these actors and witnesses will directly reveal the heterogeneous worlds of Judaism and Zionism in North Africa. The article also confirms the diversity of the French Empire despite the shared concept of assimilation and the impact of the colonial administration, that was organized in different ways depending on the local situation and on social relations in North African societies.
Keywords: Judaïsme – Djerba

Comparative Notes on the Jewish Arabic Dialects of Gabes and Djerba (Tunisia) - Gębski, Wiktor (Interconnected Traditions: Semitic Languages, Literatures, Cultures—A Festschrift for Geoffrey Khan: The Medieval World, Judaeo-Arabic, and Neo-Aramaic, 2025)
The article examines the Jewish Arabic dialects of Gabes and Djerba, two geographically proximate yet linguistically distinct varieties spoken in southern Tunisia. The study highlights significant phonological differences, such as the vowel inventory and the realisation of sibilants, with Jewish Gabes featuring three phonemic vowels and retroflex sibilants, while Jewish Djerba exhibits a reduced vowel system and fronted palatal sibilants. Syntactically, the dialects differ in their future tense markers; Jewish Gabes employs both the particle bāš and the grammaticalised participle ḥabb, while Jewish Djerba uses ḥa, possibly derived from ḥabb. Both dialects also display topicalisation strategies, including left dislocation and non-resumptive topicalisation akin to the ‘Chinese-style topic construction’. The study combines linguistic analysis with field recordings and offers insights into the diachronic and sociolinguistic aspects of these dialects, reflecting the cultural and historical dynamics of Jewish communities in North Africa.
Keywords: Judaïsme – Djerba; Linguistique – Djerba

A Paradoxical Pilgrimage. The Ghriba Synagogue in Djerba - Albera, Dionigi; Pénicaud, Manoël (Religiographies, 2022)
In North Africa, the long-term coexistence between Jews and Muslims generated many interfaith crossings. It was not uncommon for the followers of one religion to visit a shrine of the other, in order to obtain baraka (divine grace). This phenomenon has mostly disappeared throughout the Maghreb, but it persists on the island of Djerba (southern Tunisia), where over a thousand Jews are still living. Every year, for the Jewish holiday of Lag Ba’Omer, a pilgrimage gathers together thousands of Jewish pilgrims in the Ghriba synagogue. Many come from abroad, notably from France and Israel, where many Tunisian Jews migrated after the mid-20th century. Some Muslims also participate at different moments of the pilgrimage. Based on historical research and on ethnographic work carried out in 2014 and 2022, this article elucidates a series of paradoxes that make the singularity of this holy place. Here the interactions between Jews and Muslims at the shrine are characterized by an intense conviviality. Yet, during the last decades this site has been affected by tangible eruptions of bloody violence by Islamist terrorists. The structure of the pilgrimage seems to rest on a delicate balance between local and external forces. More generally, the Ghriba pilgrimage is crossed by major political dynamics, and is recurrently affected by the turmoil of the Israeli-Palestinian conflict.
Keywords: Judaïsme – Djerba

Tunisie: menace sur les juifs de l'île de Djerba - Nahum, Maya (Le Figaro, 2023)
Place: Paris
Keywords: Judaïsme – Djerba

Applying Marketing Innovation Models to Urban Events: A Comparative Study of the Ghriba Pilgrimage in Djerba - Kilani, Bochra hadj; Dhaher, Najem (Advance, 2024)
This article examines the applicability of mathematical models traditionally utilized in marketing innovation to the planning and analysis of urban events, with the Ghriba Pilgrimage in Djerba serving as a case study. Marketing innovation models, incl
Keywords: Judaïsme – Djerba; Tourisme – Djerba

Entre Kaïs Saïed et la guerre à Gaza, le malaise grandissant des juifs de Djerba - Hage, Clara (L'Orient-Le Jour, 2024)
Des autocars déversent des grappes de visiteurs à l’entrée de la Ghriba en cette après-midi mbre. Des Tunisiens des quatre coins du pays, des touristes de l’Algérie voisine et d’ailleurs raffolent...
Keywords: Judaïsme – Djerba

Il pellegrinaggio alla sinagoga della Ghriba dell’isola di Djerba - Russo, Carmelo; Nassri, Amel (Cartografie Liquide. Il Mediterraneo e le relazioni tra Italia e Tunisia, 2024)
Questo contributo si prefigge lo scopo di presentare uno fra i più noti di questi casi: il pellegrinaggio alla sinagoga della Ghriba a Djerba per la festa ebraica di Lag Ba’Omer . Si tratta di un rituale religioso in un certo senso condiviso, attraverso il quale è possibile rintracciare aspetti plurali per quanto concerne le nazionalità e le componenti religiose, incoraggiati dalla perifericità intesa in senso geografico, religioso e politico (Albera, Couroucli, 2009; Albera, Pénicaud, 2017). Lo Stato tunisino sostiene il pellegrinaggio, che trasmette un’immagine positiva del paese, in quanto luogo di tolleranza e fraternità nella diversità (Boissevain, Isnart, 2017) e favorisce un certo tipo di turismo religioso (Riecou, Souissi, 2016). Questa immagine si impone nonostante l’evento festivo sia stato macchiato a più riprese dal sangue a causa di attacchi terroristici, come quelli del maggio 2023 (Dumas, 2023), del 2002 e del 1985, oltre che percorso dai riverberi delle tensioni israelo-palestinesi, al punto che Dionigi Albera e Manoël Pénicaud (2022) riferiscono di un «Paradoxical Pilgrimage». Il capitolo si compone di tre paragrafi. Nel primo si intende analizzare i miti fondativi della Ghriba. Il secondo è dedicato alle connessioni tra dimensione religiosa e quella sociale di tale pellegrinaggio, soffermandosi sulla convivenza tra gli ebrei e i musulmani a partire dalla condivisione dei riti e delle cerimonie. Nel terzo paragrafo si vuole evidenziare come il pellegrinaggio alla Ghriba possa essere inserito in una serie di tappe che “preparano” a esso, e dunque che è inscritto in un percorso più ampio e in un processo più generale, di cui è il culmine, per altro il più importante e il suo ruolo nel potenziamento del turismo tunisino. Quello conclusivo sintetizza la multidimensionalità del pellegrinaggio e il suo ruolo nella promozione dell’economia tunisina.
Keywords: Judaïsme – Djerba; Tourisme – Djerba

Connectivités djerbiennes : globalisations méditerranéennes des Juifs de Djerba - Albera, Dionigi; Morvan, Yoann (Journal des anthropologues, 2022)
Le workshop international « Connectivités djerbiennes : Globalisations méditerranéennes des Juifs de Djerba » que nous avons co-organisé, initialement prévu en mars 2020 à l'IMéRA à Marseille, s'est finalement tenu en présentiel les 27 et 28 juin 2022. Son objectif était d'inaugurer une recherche collective et pluridisciplinaire menée dans le cadre d'un programme financé par l'A*Midex (Aix-Marseille univ.) en partenariat avec le Centre de recherche français à Jérusalem (CRFJ) et l'Institut de recherche sur le Maghreb contemporain (IRMC) à Tunis. Les difficultés d'organisation d'événements internationaux durant la pandémie COVID-19 ont conduit à reporter cet atelier au terme de ce programme, même si un certain nombre d'événements intermédiaires 3 ont permis de jalonner la mise en dialogue des différentes recherches effectuées par les membres du groupe. Celui-ci se compose d'universitaires français, israéliens et tunisiens, en mesure d'appréhender la diaspora des Juifs de Djerba dans ses points d'ancrages principaux, qui établissent entre eux diverses connectivités, et dessinent de façon originale une globalisation méditerranéenne nourrie d'échanges sud-sud.
Keywords: Judaïsme – Djerba

In Tunisia, Opening a World of Opportunities for Girls (JDC, 2021)
For the past 14 years, the JDC-supported Kanfei Yonah school in Djerba, Tunisia, has given young girls and women access to education.
Keywords: Enseignement – Djerba; Judaïsme – Djerba

Each egg, a wish on the Jewish pilgrimage to the strange Tunisian synagogue - Israel, Noticias Aurora; Abel, Pablo (2022)
Each egg, a wish on the Jewish pilgrimage to the strange Tunisian synagogue
Keywords: Judaïsme – Djerba

The Precedents and Origin of Djerba's Or Torah Fund - Picard, Joshua (2023)
Institution: The Tauber Institute for the Study of European Jewry
Keywords: Judaïsme – Djerba

دراسة انثروبولوجية للتراث الغذائي ليهود جربة - عبد العزيز, امنة (كلية العلوم الأنسانية والإجتماعية, 2022)
Keywords: Judaïsme – Djerba

‘예루살렘의 대기실’ 제르바 섬 유대 문화의 인식론적 특성 연구 A Study on the Epistemological Characteristics of Jewish Culture in Djerba Island with the ‘Antechamber of Jerusalem’ - Gidae, Lim (경희대학교 글로벌인문학술원 Cross Cultural Studies, 2022)
The Berber people, natives of the Maghreb region, are located on the island of Djerba, where Jewish culture is firmly established. In addition, traces of connection with Jerusalem, the center of the Jewish community, persist throughout the island. The island of Djerba is the only holy place for Jews outside Jerusalem. It is also well known as the ‘Antechamber of Jerusalem’ and preserves its traces relatively well. Therefore, Djerba Island is a very meaningful place as it can look at the exchanges of Jewish diaspora civilization, coexistence, and win-win relationship between Islam and Jews, and Berber. In order to understand the meaning of ‘Antechamber of Jerusalem’, this paper aims to briefly examine the Jewish situation in three Maghreb countries (Morocco, Algeria, and Tunisia) before and after French colonial rule, and to examine the current situation of Jews in the region developed in history. Next, we will assess the characteristics of the Jewish community on the island of Djerba, called the ‘Antechamber of Jerusalem’. Like the rest of the Maghreb region, the island of Djerba is also a place of cultural division. Nevertheless, the memory of Jerusalem remains the strongest in history on the island of Djerba. In this sense, it seems meaningful to examine the issue of epistemological ‘rupture or 'continuity’. This shows how Jews were able to coexist and co-exist on the island of Djerba, the ‘Antechamber of Jerusalem’, and how the French colonization and subsequent process led to a conflict and a ‘rupture’ in the coexistence. Therefore, through this paper, we will be able to understand the Jewish cultural identity of the island of Djerba, coexistence, and conflict of civilization
Keywords: Judaïsme – Djerba

베르베르와 예루살렘 관계를 통해서 본 ‘갈등과 공존’의 메커니즘 양상 The Mechanism of ‘Conflict and Coexistence’ in the Relationship between Berber and Jerusalem - Gidae, Lim; Jihoon, Kang (인문사회과학연구 Institute for Humanities and Social Sciences, 2022)
Berber and Jerusalem are not often mentioned because there is not much connection between them. This is because the existence of berber itself has not been mentioned in history. Moreover, the geographical distance from Jerusalem made it impossible to imagine the Berber connection to Jerusalem. However, 'Yennayer', the most important festival for Berbers today, mentions the ancient Pharaoh and Jerusalem. It shows that the relationship between the Berbers, Jerusalem, and the jews has existed since ancient times. This study examines the mechanism of 'conflict and coexistence' between Berber and Jerusalem from ancient times to the present. First, examine the relationship between the Berbers, Jerusalem, and Jews, focusing on the era of the Pharaoh and the era after the destruction of the Jerusalem temple. This process seems very meaningful in examining the relationship between the ancient Berbers and Jerusalem. Second, although there may have been conflicts, there are regions where the paradigm of 'coexistence' has been maintained relatively well. This is not Jerusalem, but the case of Djerba island, which contains the soul of Jerusalem, is a case in point. Although Djerba island is an islamization place, it is a unique place where is lamic ibadism, Berbers, and Jews form a 'coexistence' relationship. It examine how they were able to maintain a relationship of coexistence. Finally, we examine the conflict relationship that erupted again before and after French colonial rule. Such a process provides a meaningful interpretation in examining how the mechanism of 'conflict and coexistence' between Berber and Jerusalem has been formed, and is useful for understanding various forms of cultural exchange in the region.
Keywords: Judaïsme – Djerba

Les rituels du Shabbat chez les Juifs de Djerba - Abdelaziz, Emna (2023)
Keywords: Judaïsme – Djerba

Les Juifs Djerbiens dans le territoire militaire du sud tunisien - Elhouch, Mohamed (2023)
Keywords: Judaïsme – Djerba

Lag B'Omer festival: What is it about? (BBC, 2021)
Keywords: Judaïsme – Djerba

En Tunisie, le pèlerinage juif de la Ghriba s'ouvre sans festivités (AFP, 2021)
Le pèlerinage juif de la Ghriba, plus ancienne synagogue d'Afrique, s'est ouvert lundi sans les milliers de pèlerins venus habituellement du monde entier, en raison de la pandémie, sur ...
Publication Title: AFP Infos Françaises
Keywords: Judaïsme – Djerba

Tunisie: le pèlerinage juif de la Ghriba prévu du 25 avril au 2 mai (AFP, 2021)
Le pèlerinage juif de la Ghriba, sur l'île tunisienne de Djerba, annulé en 2020 en raison du Covid-19, est prévu du 25 avril au 2 mai, si la situation ...
Publication Title: AFP Infos Mondiales
Keywords: Judaïsme – Djerba

Jüdische Pilgerreise zur ältesten Synagoge Afrikas abgesagt (AFP, 2020)
Die jährliche jüdische Pilgerreise zur ältesten Synagoge Afrikas auf der tunesischen Insel Djerba ist wegen der Coronavirus-Pandemie abgesagt worden. "Wir werden die Synagoge erst wieder öffnen, wenn die Gefahr des ...
Publication Title: AFP - Journal Internet AFP (deutsch)
Keywords: Judaïsme – Djerba

Tunisie: annulation du pèlerinage annuel juif de la Ghriba prévu en mai (Belga, 2020)
(AFP) = Le pèlerinage annuel juif de la Ghriba, prévu du 7 au 13 mai en Tunisie, est annulé en raison de la pandémie du Covid-19, a annoncé mardi à l ...
Publication Title: Belga News Agency (français)
Keywords: Judaïsme – Djerba

Tunisie/virus: annulation du pèlerinage annuel juif de la Ghriba prévu en mai (Challenges (site web), 2020)
Le pèlerinage annuel juif de la Ghriba, prévu du 7 au 13 mai en Tunisie, est annulé en raison de la pandémie du Covid-19, a annoncé mardi à l'AFP ...
Keywords: Judaïsme – Djerba

Virus nixes Jewish pilgrimage to Tunisia's Ghriba (AFP, 2020)
The annual Jewish pilgrimage to the ancient Ghriba synagogue on the Tunisian island of Djerba has been called off because of the coronavirus pandemic, the organisers said Tuesday. Beginning 33 days ...
Keywords: Judaïsme – Djerba

Hichem Mechichi à la synagogue de la Ghriba à Djerba: La chechia chinoise fait polémique | Tekiano :: TeK'n'Kult (2021)
A l'occasion de la visite annuelle de la synagogue juive de la Ghriba, ou le pèlerinage de la Ghriba à Djerba qui a coincidé cette année avec le Ramadan 2021...
Keywords: Judaïsme – Djerba

En Tunisie, le pèlerinage juif de la Ghriba ouvert dans la sobriété - Eblotié, Guy Aimé (La Croix Africa, 2021)
Le pèlerinage juif de la Ghriba sur l’île de Djerba, en Tunisie, s’est ouvert, lundi 26 avril, dans la sobriété imposée par les mesures sanitaires
Keywords: Judaïsme – Djerba

Pèlerinage de la Ghriba-2021 : Un retour discret, mais retour tout de même - M., Ch. (Kapitalis, 2021)
Le pèlerinage de la Ghriba, dans l’île de Djerba, un des pouls principaux de l’activité touristique de notre pays, en est à sa 3e journée. À première vue, rien d’exceptionnel ne semble caractériser l’édition 2021 de cette manifestation religieuse, au contraire : le rassemblement est si timide et si peu fréquenté qu’il pourrait passer inaperçu. […]
Keywords: Judaïsme – Djerba

La peur s’installe dans la communauté juive de Djerba - Zis, Eliezer (JForum, 2021)
les Juifs tunisiens vivent à nouveau dans la peur
Keywords: Judaïsme – Djerba

Tunisie – Djerba : Annulation de toutes les festivités du pèlerinage à La Ghriba - LM (Tunisie, 2021)
Le comité du pèlerinage de La Ghriba à Djerba a annoncé, ce mardi, l’annulation de toutes les festivités relatives au pèlerinage à la Ghriba. Ne seront
Keywords: Judaïsme – Djerba

Tunisie - Israël : faut-il installer les rescapés d’Auschwitz à Djerba ? - Hanablia, Mounir (Kapitalis, 2021)
L’Etat d’Israël veut forcer la main aux Etats arabes qui ne l’ont pas encore fait, afin qu’ils se joignent au processus dit «accords d’Abraham» inauguré par les Emirats arabes unis et le Bahreïn, dans le but de régler définitivement la question palestinienne et d’assurer à Israël le marché économique nécessaire à sa prospérité. Les pressions […]
Keywords: Judaïsme – Djerba

تونس تسعى لصيانة التراث اليهودي المهدد بالضياع (ميدل ايست أونلاين, 2020)
عمليات نهب وتهريب لقطع أثرية مهمة ونادرة في تونس شاهدة على تاريخ اليهود في شمال افريقيا، ومطالبة باقامة مشروع حصر ودراسة ارثهم التاريخي والتعجيل بتشييد متحف لحمايته.
Library Catalog: middle-east-online.com
Keywords: Judaïsme – Djerba

Djerba : Life en reportage à Hara Sghira - Bourial, Hatem (Webdo, 2020)
Keywords: Judaïsme – Djerba

From bitter to sweet: The virtue of Torah and the Jewish People (Arutz Sheva, 2020)
Shavuot There is a precious custom dating back to the era of the Rishonim (1100 -1500), to eat foods made out of milk and honey on Shavuot. The source of this ...
Keywords: Judaïsme – Djerba

Annulation de la saison du pèlerinage de la Ghriba, Perez Trabelsi précise (African Manager, 2020)
Dans une intervention sur les ondes Shems FM, le président de l’Association La Ghriba à l’île de Djerba, Perez Trabelsi a indiqué, ce mercredi 1 avril 2020, que la ...
Keywords: Judaïsme – Djerba

Antisemitismus in Tunesien: Juden als Sündenböcke (Die Tageszeitung, 2021)
Antisemitismus in Tunesien: Juden als Sündenböcke Präsident Saied soll auch Juden für die sozialen Unruhen in seinem Land verantwortlich gemacht haben. Jetzt ist er um Schadensbegrenzung bemüht. Die Nationalgarde feuert während ...
Keywords: Judaïsme – Djerba

Did Tunisia’s president really make anti-Semitic rhetoric? (Arutz Sheva, 2021)
The office of the president of Tunisia defended President Kais Saied against allegations that he had blamed Jews for recent unrest. Saied “did not name any religion, no sane person would ...
Keywords: Judaïsme – Djerba

President of Tunisia apologizes to Jewish community (Arutz Sheva, 2021)
The President of Tunisia on Wednesday afternoon called the Chief Rabbi of Djerba, Rabbi Haim Bitan, and apologized for his diatribe against the Jews, faulting them for the unrest in the ...
Keywords: Judaïsme – Djerba

Ghriba, Echo de Djerba et mémoire de Lotfi Jeriri - Bourial, Hatem (Webdo, 2020)
Keywords: Judaïsme – Djerba

Djerba : Le pèlerinage de la Ghriba aurait eu lieu aujourd'hui - Bourial, Hatem (Webdo, 2020)
C’est aujourd’hui au crépuscule que commence la fête juive de Lag Be Omer à l’occasion de laquelle est organisé le pèlerinage de la Ghriba. C’est en effet trente-trois jours après Pessah que se déroule le pèlerinage annuel qui est considéré comment un temps fort du judaisme tunisien. Cette solennité qui est également dédiée au rabbin …
Library Catalog: www.webdo.tn Section: National
Keywords: Judaïsme – Djerba

Patrimoine : A Djerba, la synagogue Beit Shalom - Bourial, Hatem (Webdo, 2020)
Parmi les nombreuses synagogues de Djerba, ce lieu de culte se caractérise par des proportions modestes et une notoriété bien établie. Cette synagogue Beit Shalom se trouve à Hara Kebira, le quartier historique des juifs djerbiens. Elle est peu connue car elle est sise à l’intérieur d’une « yeshiva » c’est à dire d’une école d’apprentissage de …
Library Catalog: www.webdo.tn Section: Billets de Hatem Bourial
Keywords: Judaïsme – Djerba

À la Ghriba de Djerba : Une prière pour Bourguiba (Webdo, 2020)
Keywords: Judaïsme – Djerba

À la Ghriba de Djerba : Une prière pour Bourguiba - Bourial, Hatem (Webdo, 2020)
Durant tout le règne de Ben Ali et malgré la volonté de ce dernier de faire de l’ombre à Bourguiba, cette plaque n’a pas été descellée ou éloignée des regards. Massive écrite en arabe et en français, cette plaque en marbre se trouve à l’entrée de la synagogue de la Ghriba à Djerba. Elle exprime …
Library Catalog: www.webdo.tn Section: Billets de Hatem Bourial
Keywords: Judaïsme – Djerba

Judaïsme tunisien : A Djerba, la synagogue des Cohanim - Bourial, Hatem (Webdo, 2020)
Keywords: Judaïsme – Djerba

Les Juifs de Djerba au passé et au présent - Gozlan, Martine (Marianne, 2022)
Au musée d’Art et d’histoire du judaïsme, à Paris, une exposition consacrée au photographe Jacques Perez remet à l’honneur Djerba, sa lumière et son dernier ilot hébraïque.
Keywords: Judaïsme – Djerba

Tunisie : les dessous peu ragoûtants du pèlerinage juif de la Ghriba - Bomse, Audrey; Chabbi, Nizar (Kapitalis, 2022)
Nizar Chabbi nous a fait parvenir ce texte, co-écrit avec Audrey Bomse, avocate juive américaine de Floride, publié une première fois en mai 2014, et réécrit récemment, où il évoque les dessous peu ragoûtants du pèlerinage juif à la synagogue de la Ghriba, à Djerba, en Tunisie. La normalisation du président Kaïs Saïed, le plus...
Keywords: Judaïsme – Djerba

Le pèlerinage de Lag Baomer sur l'île de Djerba : folklore, superstition ou happening social ? - Schmidt, Armand (2023)
Après l'envoi de cartes postales de Tunisie et un rapide aperçu historique de la communauté juive en Tunisie, sans oublier la rivalité entre les "Twansa" et les "Grana", nous découvrirons la synagogue de "la Ghriba" et nous participerons à la célébration d'un évènement marquant de l'une des dernières communautés juives en terre d'Islam : le pélerinage annuel de Lag Baomer sur l'ile de Djerba, en souvenir de Shimon bar Yochaï.
Keywords: Judaïsme – Djerba

Quand les musulmans et les juifs chantent le patrimoine liturgique de Djerba - Ghrab, Mohamed (2022)
Keywords: Judaïsme – Djerba

La synagogue Pariente à Houmt Souk - Achouch, Ishak (2022)
Keywords: Judaïsme – Djerba

Quand les musulmans et les juifs chantaient le patrimoine liturgique de Djerba - Davis, Ruth Frances (2022)
Keywords: Judaïsme – Djerba

Témoignage sur la musique juive à djerba en 1978 - Davis, Ruth Frances (2022)
Keywords: Judaïsme – Djerba; Musique – Djerba

Permanence de la littérature judéo-arabe en Tunisie : les bulletins hebdomadaires de la communauté juive de Djerba - Taïeb, Yohann (2022)
Keywords: Judaïsme – Djerba

Le patrimoine immatériel des Juifs de Djerba - Hammi, Yosr (2022)
Keywords: Judaïsme – Djerba

Juifs de Djerba et stratégies identitaires - Merimi, Mohamed (Ibadica, 2020)
Ce livre est l'aboutissement d'une longue recherche engagée depuis le début des années 1990. Notre but était de comprendre la pérennité de la communauté juive de Djerba et d'expliquer la force de ses traditions. Jusqu'au XVIIIe siècle, l'île a connu un modèle de société bien particulier incarné par les ‘azzaba, un pouvoir ibadite puissant, dominant tout à la fois la population locale et la diaspora. Les Juifs occupaient une place importante dans cette organisation : des siècles durant, ils ont partagé une belle entente avec les Berbères ibadites, à tel point que l'on a parlé de « symbiose judéo-ibadite ». La situation a ensuite évolué, à cause notamment de la présence croissante sur l'île des malékites et des Arabes. L'environnement est devenu progressivement plus hostile vis-à-vis des Juifs, l'État se montrant toujours plus envahissant. Les Juifs se sont alors trouvés dans l'obligation d'adapter systématiquement leur stratégie identitaire pour se protéger contre les nouveaux dangers qui les menaçaient. L'invention du pèlerinage de la Ghriba a fait partie intégrante de cette nouvelle politique. Par le prisme de la communauté juive, ce livre retrace l'histoire de l'île du Moyen Âge à nos jours. Le lecteur y découvrira la complicité entre les deux groupes religieux ibadite et juif, l'évolution des agglomérations de Hara Kbira, Hara Sghira et Houmt Souk, les mystères de la Ghriba et tant d'autres choses qui éclairent d'un œil neuf la riche histoire de Djerba
Keywords: Bin Ya'lâ; mosquée (Erriadh; Djerba); Ghuraba; mosquée al- (Houmt Souk; Djerba); Judaïsme – Djerba; Monuments – Djerba

Rabbi Rahamim hai Hawita Hacohen (Mille-feuille du Chabbath, 2020)
Keywords: Judaïsme – Djerba

La Ghriba Djerba, Tunisia - Lellouche, Jules (Catastrophe and rebirth: 1939-1973, 2020)
Keywords: Judaïsme – Djerba

Le pèlerinage juif de la Ghriba, la plus ancienne synagogue d'Afrique, attire les touristes - Munezero, Rosine (2021)
Le pèlerinage juif de la Ghriba, la plus ancienne synagogue d'Afrique, s'est ouvert lundi sans les milliers de pèlerins venus habituellement du monde entier, en raison de la pandémie, sur l'île de Djerba, dans le sud de la Tunisie. Le point avec Rosine Munezero.
Keywords: Judaïsme – Djerba

Les rituels juifs à Djerba - Touihri, Wafa (Chema Editions, 2020)
Keywords: Judaïsme – Djerba

Minorités religieuses et dynamiques identitaires en Tunisie: Ibadites et Juifs à l'épreuve du tourisme et de la révolution - Boussetta, Mourad (Université de Laval, 2020)
Dans cette recherche, j’étudie les dynamiques identitaires des minorités ibadite/berbère et juive de l’île de Djerba (Tunisie) à travers le prisme du tourisme et de la révolution. Je démontre que l’agencéité de ces deux minorités ethnico- religieuses se base sur la force mobilisatrice de leur patrimoine immatériel. Je déconstruis le double discours colonial et national les dotant d’un statut historique et juridique subalterne en me basant sur l’apport critique des études postcoloniales et sur une ethnographie multi-située. J’inscris ce faisant cette agencéité dans une dynamique de relations de pouvoir. J’analyse les adaptations, les négociations et les résistances des acteurs ibadites/berbères et juifs sous le régime colonial puis sous l’État-nation pour aboutir à une meilleure connaissance de leurs stratégies dans l’hyperprésent, soit la révolution de 2011. J’explique qu’en contribuant activement au jumelage de leur patrimoine immatériel à l’industrie touristique et qu’en s’engageant dans la mouvance politique postrévolutionnaire, ces acteurs se réapproprient une citoyenneté entière en Tunisie. Cet examen critique met en évidence les stratégies adoptées par les acteurs des minorités étudiées pour se repositionner par rapport aux structures, non pas dans le sens d’une rupture, mais plutôt dans celui de s’insérer dans les relations de pouvoir avec un statut avantageux.
Keywords: Judaïsme – Djerba; Tourisme – Djerba

WORKSHOP : « Connectivités djerbiennes. Globalisations méditerranéennes des Juifs de Djerba » (26 novembre 2020) (CRFJ.org, 2020)
Jeudi 26 novembre 2020 - Le projet vise à entamer une enquête exploratoire et pluridisciplinaire sur les Juifs de Djerba en Méditerranée (Djerba, Marseille, Israël). Il s’appuie sur et rend hommage au travail de Lucette Valensi, et à son étude monographique (avec Abraham Udovitch, 1984) des « Last
Library Catalog: www.crfj.org
Keywords: Judaïsme – Djerba

The Halachic Approach of Rabbi Moshe Chalfon Ha'kohen From Djerbah As it Reflected in his Halachic writings- 'Brit Kehuna' And the Responsa 'Shoel V'Nishal' - Mamo, Shai (Universität Potsdam, 2020)
This work is focused on the Halachic Approach of Rabbi Moshe Chalfon HaCohen from Djerbah. Rabbi Moshe Chalfon HaCohen was born in 1874 and died 1950. He was appointed Chief Rabbi of Djerbah, an island near Tunisia, in 1935, and is considered to have been one of the greatest rabbis of North Africa, particularly of Tunisia and Djerbah. With the French occupation of Tunisia in 1881, French culture, technological innovations and modernity penetrated the community. All of these affected life in Djerbah and the rabbis, including Rabbi Chalfon, needed to relate to this new situation. This research deals with two of Rabbi Chalfon’s essays dealing with Halachic responsa: “Brit Kehuna” – a compilation of the Halachic responsa and customs of the Jewish community in Djerbah, and “Shoel Venishal,” a book of Halachic responsa which deals with questions and his answers. Among other aspects, this research shows Rabbi Chalfon's unique emphasis on the humane aspects of Halacha and his ability to utilize them versus formal considerations.
Keywords: Judaïsme – Djerba